Meneropong dengan Kolom - Mahfudz, Ahmadul Faqih (MAARIF Institute, 2023)
Ahmad Syafii Maarif is one of the many icons of religious, national and humanitarian thought in Indonesia. His thoughts were welcomed when he was named general chairman of the Muhammadiyah Central Leadership. His position as a thinker and mover is increasingly mature because the figure who is often called Buya Syafii is also a prolific columnist in various mass media such as newspapers. The columns are poignant and charming because they are sprinkled with poetry and proverbs.